2004
DOI: 10.1038/sj.pcan.4500718
|View full text |Cite
|
Sign up to set email alerts
|

External beam radiation therapy after radical prostatectomy: efficacy and impact on urinary continence

Abstract: Introduction and Objectives: The efficacy of adjuvant and salvage external beam radiation (AXRT þ SXRT) for prostate cancer after radical prostatectomy (RP) has been debated because of the inability to rule out systemic occult metastasis, uncertainty that radiation eradicates residual local disease and the potential of exacerbating impotency and incontinence. To characterize the effectiveness and treatment morbidity a retrospective review was performed. Methods: In all, 38 patients received AXRT and 91 receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
(20 reference statements)
0
8
2
Order By: Relevance
“…175 Fontaine et al 176 also reported no change in continence status in 16 of 17 men after salvage radiation. However, Petroski et al 177 reported that post-operative radiotherapy worsened continence in 26% of 129 patients followed for a median of 5 years. On the other hand salvage RP following EBRT has been has been generally reported to have a high incidence of urinary incontinence 178 -180 possibly because of radiationinduced fibrosis of the external sphincter.…”
Section: Incontinence After External Beam Radiotherapy Alone and In Cmentioning
confidence: 99%
“…175 Fontaine et al 176 also reported no change in continence status in 16 of 17 men after salvage radiation. However, Petroski et al 177 reported that post-operative radiotherapy worsened continence in 26% of 129 patients followed for a median of 5 years. On the other hand salvage RP following EBRT has been has been generally reported to have a high incidence of urinary incontinence 178 -180 possibly because of radiationinduced fibrosis of the external sphincter.…”
Section: Incontinence After External Beam Radiotherapy Alone and In Cmentioning
confidence: 99%
“…Urinary continence can improve for up to 24 months after RP and early RT may interfere with or prolong this return to continence. 19 In this study, UI was more common in the early RT group at the time of RT and UI rates improved in both groups at years 1, 2, and 3 post-RT. Although the severity of UI was not recorded, only 12 patients in the cohort had an AUS placed.…”
Section: Complications Of Radiotherapy After Prostatectomymentioning
confidence: 68%
“…As such, adjuvant RT is frequently delayed after RP to allow for wound healing and return of urinary continence. 19 In this study, the mean time to RT in the early group was 3.6 months with a range of 1-5 months indicating that some patients received RT earlier than recommended. Patients who received early RT in our series either opted for adjuvant RT or exhibited early biochemical relapse, whereas those who received late RT generally exhibited late relapse or a relapse with a slow doubling time.…”
Section: Complications Of Radiotherapy After Prostatectomymentioning
confidence: 95%
“…EAU guidelines currently recommend radical prostatectomy only in patients with PSA <20 ng/mL 6 . Adjuvant radiotherapy for these patients can worsen the continence rates 7 . Recently, opinion in favor of radical prostatectomy as a part of a multimodality approach in patients with locally advanced disease has been progressively increasing 9 …”
Section: Discussionmentioning
confidence: 99%
“…Although adjuvant radiotherapy could be considered for patients with positive margins and high risk of biochemical recurrence, concern prevails about the worsening of urinary continence. 7 On this background , we present our experience of MIRP in this subgroup of patients including the operative, pathological and short-term oncological outcomes.…”
Section: Introductionmentioning
confidence: 99%